Effect of Non-Genetic Factors on Seminal Traits of Indigenous and Crossbred Bulls under Semi-arid Climatic Conditions - Meena, Sunil Kumar; Sharma, Prakash Chandra; Saini, Samita; Gahan, Mukesh Kumar; Swami, Priyanka; Gurjar, Devkishan; Chandra, Vipin (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted at Post Graduate Institute of Veterinary Education and Research (PGIVER), Jaipur, Rajasthan, India during July–December 2020 to evaluate the effects of non-genetic factors on semen characteristics of bulls. The data of 4608 ejaculates during the period of 2017–2020 from Tharparkar and its cross with Holstein, Jersey and its cross with Sahiwal cows was maintained at Frozen Semen Bank (FSB), India. The Semen characteristics were recorded and stored in Information Network for Animal Productivity & Health (INAPH) application maintained at FSB and National Dairy Development Board (NDDB). The average semen volumes were estimated as 4.18±0.02 ml. Non-genetic factors viz. season, period, breed, ejaculation order and age of bulls showed significant effects on various semen parameters. Higher estimates of semen concentration, motility, Total Ejaculation Volume (TEV) and Post-thaw Motility (PTM) were recorded in Jersey Sahiwal crossbred bull whereas semen motility was observed as higher for Tharparkar bull. Seasonal analysis revealed that winter and autumn were favorable seasons for higher quantity and quality semen production. Age wise analysis presented significantly increased values with the increasing age except semen motility. Non-genetic factors under semi-arid climatic conditions revealed significant effects on semen characteristics of exotic, crossbred and indigenous genotypes and need to be accounted for quality semen production in a semen production centre. Present findings indicate that Jersey Sahiwal cross bulls were found better for quality semen production under semi-arid climatic condition than exotic and other crossbreed bulls.